The archive of life : adapting a Foucaultian power and powerlessness of society with a focus on Alice Springs - Head, Richard Michael (Common Ground Publishing, 2018)
"The book is an explanation of society creating its evolving landscape utilising one place Alice Springs as a focused example over time, but of how the place developed through multiple resistances flowing back and forth from bottom up and top-down. From this theoretical/concrete background the book aims to look at how power operates over time to ensure that society is an ongoing concern, and the imagining of a power behind the scenes that saturates and drives the whole process. In essence, bringing one closer to the Truth of the matter. Following its colonial beginnings as a tentative toe hold within the Central Australian landscape to a fully developed representative of Western capitalism today, Alice Springs makes an ideal living laboratory of how contemporary society evolves and is. The presence of this laboratory of life is too good a reason not to address the meaning that is the Archive of Life"--